REVIEW D. Brown, F. Macpherson (eds.), The Routledge Handbook of Philosophy of Colour, Routledge, London 2020, pp. 496, ISBN 9780415743037 (Itinera, 2020)
«Why has the examination of many different aspects of colour been a prominent feature in philosophy, to such an extent that the topic is worthy of a handbook?». This is the question that opens the editors’ introduction to The Routledge Handbook of Colour, whose imminent publication we are happy to announce here.
Keywords: philosophy of colour, Handbook, publication, colour experience